2016
DOI: 10.9738/intsurg-d-15-00105.1
|View full text |Cite
|
Sign up to set email alerts
|

Compliance and Surgical Team Perceptions of WHO Surgical Safety Checklist; Systematic Review

Abstract: This systematic review aimed to assess surgical safety checklist compliance and evaluate surgical team perceptions and attitudes, post-checklist implementation in the operating room. The World Health Organization (WHO) surgical safety checklist (SSC) has decreased complications and mortality. However, it is unclear whether this reduction is influenced by the vicarious enhancement in teamwork, communication, and staff awareness established by SSC implementation. The preferred reporting items for systematic revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 47 publications
0
21
0
6
Order By: Relevance
“…This Program aims at reducing the number of deaths and surgical complications such as performing surgery on the patient or wrong location and inadvertent retention of foreign bodies. Thus, the checklist aims to reinforce patient safety practices and promote better communication among health professionals (22)(23) .…”
Section: Development Of Continuing Education Actionsmentioning
confidence: 99%
“…This Program aims at reducing the number of deaths and surgical complications such as performing surgery on the patient or wrong location and inadvertent retention of foreign bodies. Thus, the checklist aims to reinforce patient safety practices and promote better communication among health professionals (22)(23) .…”
Section: Development Of Continuing Education Actionsmentioning
confidence: 99%
“…The "Sign-In" review was seen as redundant, coinciding with former arguments of SSC performance being double checking routines. ( (17,46) In addition to the narrower and wider risk perceptions, we found that SSC utilisation is also a function of how it is incorporated into team membersʼ workflow schedules in OT, and how much effort has been spent reducing practical barriers within the team. (47) This finding corroborates previous investigations.…”
Section: Discussionmentioning
confidence: 92%
“…Der Vergleich mit der internationalen Literatur bezogen auf Compliance-Raten hinsichtlich der Präsenz der »Surgical-Safety-Checklist« im chirurgischen Setting erbringt eine äußerst inhomogene Datenlage. So beträgt in den Übersichtsarbeiten von 2014 aus neun spanischen Krankenhäusern und aus 2016 mit 13 Studien die Spannbreite der Compliance-Raten zur Anlage der SSC zwischen 63,7 und 100,0 % [18,26] Vilz et al (2016) dokumentierten für eine vergleichbare nationale Einrichtung der universitären Maximalversorgung folgende Werte für die Anwendung der Phasen: »Sign-In« 48,0 % in 2010 und 83,0 % in 2012, bzw. »Team-Time-Out« 35,0 % und 63,0 % für die analogen Zeiträume [28].…”
Section: Diskussionunclassified
“…Mit dem positiv veränderten Heilverlauf korreliert eine Erhöhung der Sicherheitskultur im OP-Saal, die arbeitspsychologisch durch eine veränderte Wahrnehmung des Stellenwerts von Teamarbeit begründet wird und als Nebeneffekt der Checkliste gilt [14,17]. Die WHO schätzt, dass durch die konsequente Umsetzung der SSC mindestens 500 000 Todesfälle pro Jahr weltweit vermieden werden könnten [18,19].…”
Section: Introductionunclassified